La gestión de derechos de autor en entornos digitales, un reto para las bibliotecas y centros públicos de información - Ramos Simón, Fernando (Revista General de Información y Documentación, 2002)
This article studies the appearance or mechanisms for the management of intellectual property rights in the electronic information market and their implications for libraries and public information centers. The study tackles the implications of proecting digital content on the economic and service model of these institucions as well as on traditionally recognized users’ rights. The study of the legal regulation which is under way in the United States and the European Union emphasizes the role which has been assigned in North America to the Library of Congress for the drawing up of standards which take into account exceptions to the protection of content.
Keywords: Intellectual property; author’s rights; digital libraries; cyberspace; electronic information market; digital rights management (DRM)